2013
DOI: 10.1371/journal.pone.0057682
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive and Targeted Gene Delivery into the Brain Using Microbubble-Facilitated Focused Ultrasound

Abstract: Recombinant adeno-associated viral (rAAV) vectors are potentially powerful tools for gene therapy of CNS diseases, but their penetration into brain parenchyma is severely limited by the blood-brain barrier (BBB) and current delivery relies on invasive stereotactic injection. Here we evaluate the local, targeted delivery of rAAV vectors into the brains of mice by noninvasive, reversible, microbubble-facilitated focused ultrasound (FUS), resulting in BBB opening that can be monitored and controlled by magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 52 publications
4
76
0
Order By: Relevance
“…We demonstrated that the transduction observed 2 days after BBB opening had a relative intensity that was 5-fold greater than that of the LpDNA only. The in vivo enhancement of transgene expression in the BBB-opened brain was consistent with our previous results that showed drugs and genes can be deposited at higher concentrations into targets by FUS-induced BBB opening [12,15], demonstrating the stability and repeatability of this FUS-BBB opening technique. We have proven that LpDNA with FUS sonication produces sufficient plasmid deposition to express both luciferase and GDNF production (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We demonstrated that the transduction observed 2 days after BBB opening had a relative intensity that was 5-fold greater than that of the LpDNA only. The in vivo enhancement of transgene expression in the BBB-opened brain was consistent with our previous results that showed drugs and genes can be deposited at higher concentrations into targets by FUS-induced BBB opening [12,15], demonstrating the stability and repeatability of this FUS-BBB opening technique. We have proven that LpDNA with FUS sonication produces sufficient plasmid deposition to express both luciferase and GDNF production (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Most strategies have utilized viral vectors to deliver therapeutic genes through BBB opening [11,12]. However, there is little information available on delivery to the brain using non-viral vectors, the relevance of plasmid sequestration in liposomes on the localized transgene expression, or the effect of this treatment on transduction of genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] For the relatively larger-size dextrans (500 and 2,000 kDa), IC was found to be the main mechanism for their successful trans-BBB delivery. Cavitation detection has not been reported in previous studies of FUS-enhanced delivery of larger agents, such as antibodies 4,[32][33][34] and gene vectors, 5,35,36 whose MWs are on the same scale as the 500 and 2,000 kDa dextran, respectively. The MI of the FUS used in those studies varied within the range of 0.63 to 1.56, and the MI corresponding to 0.84 MPa (1.5 MHz) in our study was 0.69, which was in the lower end of the aforementioned range.…”
Section: Microbubble Cavitation Emissionsmentioning
confidence: 84%
“…74 Overall, the evidence supports the use of microbubble-enhanced focused ultrasound to locally and temporally disrupt the BBB to deliver viral vectors. 75 A second, less popular, but very interesting, way to physically open TJs is using electromagnetic waves. 76 A recent in vitro study 77 demonstrated that exposure to electromagnetic pulses can affect key TJ-related proteins, including ZO-1, occludin, and claudin-5.…”
Section: Biological Stimulimentioning
confidence: 99%